Efficient Multigram Syntheses of Air-Stable, Chiral Primary Phosphine Ligand Precursors via Palladium-Catalyzed Phosphonylation of Aryltriflates - Ficks, Arne; Sibbald, Connor; Ojo, Stephen; Harrington, Ross W.; Clegg, William; Higham, Lee J. (Synthesis, 2013)
Air-stable, chiral primary phosphines have been synthesized on a multigram scale. The key synthetic step is an optimized palladium-catalyzed phosphonylation reaction of aryltriflates, which opens up a valuable synthetic route to a chiral scaffold that is easily derivatized into novel phosphines.
Keywords: phosphorus; palladium; cross-coupling; asymmetric catalysis; air-stability